Accounting for Inequality in India: Evidence from Household Expenditures - Cain, J. Salcedo (2012)
We utilize household-level consumption expenditure data from India to examine the evolution of inequality during 1983-2004. Various measures of inequality show that inequality levels were relatively stable during 1983-93, but increased during 1993-2004. The increases in inequality have not precluded reductions in poverty, however. They are also more of an urban phenomenon and can be accounted for by increases in returns to education in the urban sector to a considerable extent, especially among households that rely on income from education-intensive services and/or education-intensive occupations. Some of the increases in the returns to education can be linked to economic liberalization undertaken in the 1990s.